2003
DOI: 10.1080/01411920301854
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and High Attainment

Abstract: Recent emphasis on raising attainment has focused attention onto the 'gender gap' in school attainment levels. Using data from the Scottish School Leavers Survey, the article examines factors related to high attainment and asks whether these differ for males and females. A strong relationship is established between social advantage and high attainment within each gender. There is no evidence of differential progression rates for males and females between the ages of 16 and 18. The only factor which offers any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 18 publications
3
33
0
3
Order By: Relevance
“…Female students had higher study habits scores than male students and it was similar with the findings of Hong and Lee, 2000;Tinklin, 2003;Anton and Angel, 2004;Houtte, 2004;Sud and Sujatha 2006. Further from data analysis it came into light that a significant relation exists between Study habits and Socio-economic status of secondary school students. It was found that male and female students differ in their SES, especially female students had higher SES than male students.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Female students had higher study habits scores than male students and it was similar with the findings of Hong and Lee, 2000;Tinklin, 2003;Anton and Angel, 2004;Houtte, 2004;Sud and Sujatha 2006. Further from data analysis it came into light that a significant relation exists between Study habits and Socio-economic status of secondary school students. It was found that male and female students differ in their SES, especially female students had higher SES than male students.…”
Section: Discussionsupporting
confidence: 86%
“…When the differences were examined in terms of gender, Pillai (2012) observed that significant difference exists in the study habits of male and female students moreover research studies revealed that female students were more successful academically than their male counterparts and they have better study habits and attitudes (Tinklin, 2003;Hong and Lee, 2000;Anton and Angel, 2004;Houtte, 2004;Sud and Sujatha, 2006) It is globally suggested that social-economic status is the key factor in academic performance, Caldas and Bankston 1997; Alam 2006 found that Socio-economic status is significantly related with students' academic achievement and Suleman et al (2013) in his study concluded that parental Socio-economic status; their educational, occupational and income level affects the academic achievement of students at secondary level. Sirin (2005) conducted a meta-analytic review of research on SES and academic achievement in journal articles published between 1990 and 2000.…”
Section: Research Articlementioning
confidence: 99%
“…Comments such as "well, boys are just naturally good" and "I'm not sure I could do physics at uni" suggest that many still perceived a gender divide in favour of males with respect to achievement in physical and mathematical sciences, accounted for by natural ability, rather than effort (e.g. Tinklin 2003). Students also commented that they were frustrated by family members who viewed physics as a boys' subject and questioned their choice of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that prior to the 1970s, boys and girls were educated for very different occupational and domestic roles (Riddell 2000), while the 1975 Sex Discrimination Act made it unlawful to treat girls differently from boys regarding access to courses, and educational and occupational opportunities. On the other hand, continuing inequalities and persistent disadvantages for women regarding subject choice and opportunities in higher education and socio-economic status attainment have received less attention (Francis 2002;Marini and Fan 1997;Tinklin 2003). Although women make up more than half of higher education students and almost half of the labour force, proportionately fewer women than men rise to the top of their professions (Crompton 2006;Farmer 1997Farmer , 2006.…”
Section: Gender Differencesmentioning
confidence: 99%